Gastroenterology clinics of North America : women's issues in gastroenterology - Ahmad, Asyia; Bayat, Hasan;Beaulieu, Dawn B.;Bhandari, Bhavik M.;Choudhary, Cuckoo;Crowe, Sheila E.;Esposti, Silvia Degli;Elta, Grace H.;Ahmad, Asyia ;Frank, Barbara B. (Philadelphia, Pennsylvania : Saunders, 2011)
Discusses issues in gastroenterology unique to female patients. This title features articles that help readers to determine whether gender influences diagnosis and treatment of functional disorders, evaluate problems in the pregnant patient, explain immune diseases of the GI, and discuss unique genetic aspects of Lynch Syndrome and IBD.
Treatment of irritable bowel syndrome in women -- When to reconsider the diagnosis of irritable bowel syndrome -- Nausea adn vomiting of pregnancy -- Liver disease in oregnancy -- Hepatitis B in pregnancy: challenges and treatment -- Primary biliary cirrhosis -- Special considerations for women with IBD -- Inflammatory bowel disease in pregancy -- Issues related to colorectal cancer and colorectal cancer screening -- A global perspective on gastrointestinal disease -- The challenges of being female gastroenterologist -- Gastrointestinal issues in older female patient
Includes bibliographical references and index.
Keywords: GASTROINTESTINAL DISEASES